Case report: Ultrasound biomicroscopy as a guide for the selection of injection sites for dexamethasone intravitreal implant (Ozurdex) for peripheral granulomatous ocular toxocariasis in children - Zhang, Xin; Hou, Xinzhu; Zhang, Yan; Liu, Jingjie; Zhang, Zhiyong (Frontiers in Medicine, 2023)
Purpose: This article aims to report a case of successful treatment of peripheral granulomatous ocular toxocariasis (OT) in an 8-year-old patient using intravitreal injection of dexamethasone (DEX) implant (Ozurdex) under ultrasound biomicroscopy (UBM) guidance. Case presentation: A previously healthy 8-year-old boy with a history of long-term close contact with dogs complained of blurring of vision in the right eye for a year. Ophthalmic examination of his right eye showed chronic uveitis. Notably, UBM examination identified granulomas and peripheral vitreous strand in the ciliary body from 3 to 8 o'clock positions. Enzyme-linked immunosorbent assay (ELISA) results of the intraocular fluid (IF) and serum showed increased anti-Toxocara immunoglobulin G (IgG) levels, leading to a diagnosis of peripheral granulomatous OT in the right eye. Intraocular surgery was not indicated in this case. The treatment goal was to alleviate uveitis, improve visual acuity, and prevent complications. He was treated with an intravitreal injection of DEX implant, administered as a single dose every three months, total two doses, combined with albendazole, an oral anthelmintic. Under preoperative UBM guidance, two injections were performed at the 12 and 10 o'clock positions in the pars plana where there were no granulomas and peripheral vitreous strand, successfully preventing complications associated with intravitreal injection. After two injections, the patient's right eye vision improved significantly, with the best-corrected visual acuity (BCVA) increasing from 20/400 to 20/50. Vitreous opacity and retinal edema were reduced, preretinal proliferative membrane was stabilized, and no adverse events occurred. Conclusion: UBM can accurately determine the location and extent of peripheral granulomas in OT patients, facilitating the avoidance of granulomas during intravitreal injection and preventing complications associated with intravitreal injection. Under the close follow-up and strict adherence to indications, preoperative UBM-guided intravitreal injections of DEX implant treatment for pediatric peripheral granulomatous OT are safe and effective, providing a new therapeutic option for pediatric peripheral granulomatous OT.